2019
DOI: 10.9767/bcrec.14.3.4395.586-603
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(0) Nanoparticles Immobilized onto Silica/Starch Composite: Sustainable Catalyst for Hydrogenations and Suzuki Coupling

Abstract: The present paper aims to give insight into the art in the field of the synthesis, characterization and applications of Pd(0) nanoparticles immobilized onto silica/starch composite (SS-PdNPs) for hydrogenations and Suzuki coupling. Metal(0) nanoparticles immobilized onto silica/starch composite [SS-MNPs] were prepared from different metal acetylacetonate complexes [Co(acac)2], [Cu(acac)2], [Pd(acac)2],  [Ru(acac)3], [Mn(acac)3], [Co(acac)3] by immobilizing onto silica/starch composite, followed by reduction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…According to the procedure developed by Panah's group for the synthesis of a silicastarch substrate-derived catalyst PNP-SSS, Sodhi et al immobilized palladium nanoparticles onto the same silica starch composite (SS) by treatment with Pd(acac) 2 and NaBH 4 as the reducing agent [63]. Data obtained from TEM analysis indicated for SS-PdNPs, an average size of Pd(0) nanoparticles around 3.5 nm.…”
Section: Cross-coupling Reactions Promoted By Palladium Catalysts Sup...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the procedure developed by Panah's group for the synthesis of a silicastarch substrate-derived catalyst PNP-SSS, Sodhi et al immobilized palladium nanoparticles onto the same silica starch composite (SS) by treatment with Pd(acac) 2 and NaBH 4 as the reducing agent [63]. Data obtained from TEM analysis indicated for SS-PdNPs, an average size of Pd(0) nanoparticles around 3.5 nm.…”
Section: Cross-coupling Reactions Promoted By Palladium Catalysts Sup...mentioning
confidence: 99%
“…It is a natural polymer employed in the food industry as a gelling, thickening, stabilizing Scheme 13. Suzuki-Miyaura coupling of aryl bromides with phenylboronic acid promoted by palladium nanoparticles immobilized on silica-starch composite (SS-PdNPs), reported in 2019 by Sodhi and co-workers [63].…”
Section: Cross-coupling Reactions Promoted By Palladium Catalysts Sup...mentioning
confidence: 99%
“…The catalytic performance of Pd 0 particles immobilized on a silica/starch composite material was investigated by Sodhi and Paul. [128] The catalyst was prepared by impregnation of a silica/ starch composite with Pd(acac) 2 in ethanol, followed by reduction of the precursor with NaBH 4 , which afforded catalyst Pd 0 -20-starch-mSiO 2 with a Pd loading of 1.8 wt%. SEM images indicated that the sample had a porous structure and Pd particles of 3.5 nm were formed.…”
Section: Other Silica-supported Catalystsmentioning
confidence: 99%
“…Sodhi et al . reported Pd(0) nanoparticles immobilized onto silica/starch composite (SS‐PdNPs) for hydrogenation of nitroarenes and α , β ‐unsaturated compounds using molecular hydrogen [29] …”
Section: Introductionmentioning
confidence: 99%